The Influence of Viral Marketing and Influencer Marketing on Purchase Intention through a Skincare TikTok Account - Luthpiyah Juliandara; Ali Nur Hakiki; Kurniawati Mulyanti; Evi Mafriningsianti (AIBPM Publisher, 2024)
Skintific_ID's skincare marketing has utilized viral marketing and influencer marketing strategies through the social media platform TikTok. Despite achieving second place in market share, Skintific_ID continues to face stiff competition from its main competitor, Somethinc. To address this gap, this research focuses on viral marketing and influencer marketing strategies. The purpose of this study is to analyze the effect of viral marketing and influencer marketing on the purchase intention of the @skintific_id TikTok account. The research method used is a quantitative method with a causal associative research design. The sample consisted of 100 respondents selected through purposive sampling. The results showed that viral marketing and influencer marketing together have a significant effect on purchase intention. However, when considered individually, only influencer marketing has a significant effect on purchase intention, while viral marketing has no significant effect. To improve the marketing strategy, Skintific is advised to improve the content on the @skintific_id TikTok account with creative and informative videos and provide updated training to the marketing team on viral and influencer marketing strategies. In addition, they should select influencers that align with the company's vision and expand promotion to other platforms such as Instagram and YouTube.